2013
DOI: 10.1017/s1742170513000252
|View full text |Cite
|
Sign up to set email alerts
|

Maize silage and Italian ryegrass silage as high-energy forages in organic dairy cow diets: Differences in feed intake, milk yield and quality, and nitrogen efficiency

Abstract: During the winter feeding period in organic dairy production systems in the alpine and pre-alpine regions of Austria and its neighboring countries, maize silage is an energy-rich forage that is regularly included in grass-silage-based diets to improve the energy supply of the cows. Italian ryegrass (Lolium multiflorum Lam.) is also a high-energy fodder grass popular as forage for dairy cows, but it is rarely cultivated in Austrian organic agriculture. The two crops differ in their cultivation demands and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Several researchers have documented the effect of various feed types on the resulting FA profiles of milk. These experiments have shown that cattle breed, FA content in the feed, and ruminal digestion are all factors that can influence the FA content in milk (Egger et al, 2009;Hristov et al, 2011;Baldinger et al, 2014;Samková et al, 2014). For example, Steinshamn (2010) reviewed experimental data from feeding trials using a variety of grassland legumes such as white clover, red clover, and lucerne and demonstrated that, in general, a difference in feed resulted in changes to the FA composition of milk when compared with the control.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have documented the effect of various feed types on the resulting FA profiles of milk. These experiments have shown that cattle breed, FA content in the feed, and ruminal digestion are all factors that can influence the FA content in milk (Egger et al, 2009;Hristov et al, 2011;Baldinger et al, 2014;Samková et al, 2014). For example, Steinshamn (2010) reviewed experimental data from feeding trials using a variety of grassland legumes such as white clover, red clover, and lucerne and demonstrated that, in general, a difference in feed resulted in changes to the FA composition of milk when compared with the control.…”
Section: Introductionmentioning
confidence: 99%
“…Corn silage is an energy-rich forage that is often included in grass-silage-based diets to improve the energy supply in cows. Moreover, the inclusion of corn silage in the diet increases the supply of fermentable carbohydrates in the rumen [ 8 ]. In Korea, the production of IRG and corn accounts to 53.1% and 4.4%, respectively, of the total forage produced in 2013 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of drought resistance corn breed (Lathrop & Namuth, 2011), whole crop sorghum silage (Colombini et al, 2015;Cattani et al, 2017;Khosravi et al, 2018), high sugar forage sorghum silage (Su-jiange et al, 2016) as well as sorghum and Sudan grass in a drought prone region (Getachew et al, 2016) is an indicator for imminent need of alternative forage. The use of cereals silage is also popular now (Van Duinkerken et al,1999;Bernard et al, 2002;Baldinger et al, 2011Baldinger et al, , 2014Harper et al, 2017, Orosz et al, 2019. However, the use of Italian ryegrass and winter cereals for silage is not reported until today.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of Italian ryegrass and winter cereals for silage is not reported until today. Italian ryegrass (Lolium multiflorum) is one of the fastest growing grass species with excellent nutritional qualities particularly high fiber digestibility (NDFd), CP and sugar content (Baldinger et al, 2011(Baldinger et al, , 2014Field crop news, 2014;DLF seeds, UK, 2018;Byron Seeds, LLC, 2019). Field crop news (2014) reported that the yield of Italian ryegrass is not as high as winter cereals such as oats, but nutrient quality and palatability is greater which makes it more suitable for high producing dairy cow feed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation